Fracionamento granulométrico e micronização como estratégia para agregação de valor ao bagaço de oliva: compostos bioativos e bioacessibilidade - Speroni, Caroline Sefrin (2019)
The objective of this study was to evaluate the effects of granulometric fractionation and micronization of olive pomace as a strategy to improve the functional and technological properties of dietary fiber and polyphenol bioaccessibility. Crude olive pomace was separated into 2 mm sieves resulting in F1 (> 2 mm) and F2 (< 2 mm). The micronized samples were defatted and a factorial design was conducted aiming to increase the extractable polyphenol (EPP) content, testing rotation and milling time. Thus, F1 presented higher EPP content using 500 rpm/24.8 min and F2 at 500 rpm/16 minutes. Micronized samples reduced the average particle size to 30 μm. Micronization increased the EPP (1.7 g 100 g-1 to 2.0 g 100 g-1) and hydrolysable tannins (6.4 and 6.9 g 100 g-1, respectively) content in F1 and F2, with the consequent increase of antioxidant activity. Another experimental design using higher times of micronization was conducted aiming the reduction of IDF/SDF ratio. The lowest ratio was found after micronization at 300 rpm/5 hours for both samples (F1 and F2). This extended time treatment reduced the average particle size to 17.8 and 15.6 μm for F1 and F2, respectively. In addition, the dietary fiber content was modified, increasing the soluble dietary fiber and reducing the insoluble fraction. There was a redistribution of dietary fiber fractions, also reflecting changes in the technological and functional properties of the powders formed. These samples were submitted to in vitro digestibility assay to verify the bioaccessibility after salivary, gastric and intestinal digestion (absorbable and non-absorbable fractions). Phenolic compounds were released in the salivary phase and micronization was responsible for increasing the content of released compounds in this phase. Acid conditions in simulated gastric phase were responsible for the greatest release of phenolic compounds from all digestion stages. F1 micronization increased the digestibility of hydroxytyrosol. Oleuropein, apigenin and luteolin underwent the digestion process intact. Antioxidant capacity was higher for micronized samples in the digestion stages, due to the greater release of phenolic compounds. The use of olive pomace micronization yielded important changes in the chemical and physical composition of powder products. Through this study, it can be concluded that granulometric fractionation and micronization are efficient methods for improving the physicochemical characteristics of olive pomace, a by-product that should be used because of its polyphenol and soluble dietary fiber content, that can be a source of these compounds when used in human and animal nutrition.